The Relationship of Family Support, Maternal Readiness, and Anxiety Level of Pregnant Women Before Giving Birth - Nurhidayati Nurhidayati; Zumrotul Ula; Nasrullah Nasrullah (Sean Institute, 2023)
Childbirth is a stressful event for a mother. The greater the pregnancy period, will cause uncomfortable feelings. Many mothers experience excitement, anxiety, fear, and panic during labor. At this time, family support turns out to have an important effect on the mother's psychological condition in labor. The purpose of this study was to determine the relationship between family support and maternal readiness with the level of anxiety of pregnant women before delivery. This study used correlation research. The population in this study was pregnant women before childbirth which amounted to 37 people. The sample obtained was 25 willing respondents who met the inclusion and exclusion criteria. The sampling technique used was saturated sampling. The results showed that the highest category of husband support was 21 people (84.0%). The level of maternal anxiety facing childbirth was mostly low at 16 people (64.0%). Thus there is a tendency for pregnant women before labor with the support of their husbands tend not to worry, with a value of p = 0.004 (p < 0.05), which means there is a significant relationship between husband support and the level of anxiety of pregnant women before delivery. Based on the study's results, it is expected that the husband accompanies the wife during labor because the higher the husband's support, the lower the mother's level of anxiety facing childbirth.